2008
DOI: 10.1007/s10517-008-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antitumor activity of peptide extracts from medicinal plants on the model of transplanted breast cancer in CBRB-Rb(8.17)1Iem mice

Abstract: We studied antitumor effects of peptide extracts from plants on slowly growing mammary adenocarcinoma in CBRB-Rb(8.17)1Iem mice used as a model of breast cancer in humans. The antitumor effect of a single injection of the test peptides was evaluated by the delay of the appearance and growth of palpable breast cancer in mice over 4 weeks. Peptides from Hypericum perforatum and a mixture of Chelidonium majus L., Inula helenium L., Equisetum arvense L., and Inonotus obliquus exhibited maximum activity. Peptide ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Lee et al (2002) showed that the crude water extract of P. lactiflora inhibits growth of both HepG2 and Hep3B cell lines. The extract of I. helenium is cytotoxic to colon, breast, pancreatic, and astrocytoma cancer cell lines (Dorn et al, 2006;Tepkeeva et al, 2008). C. cassia extracts inhibit colon cancer cells and hepatocellular carcinomas, and C. cassia and A. gigas inhibit solid tumor growth (Kwon et al, 1998;Lee et al, 2003Lee et al, , 2007Moon et al, 2006) and induces apoptosis in HL-60 cells (Ka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2002) showed that the crude water extract of P. lactiflora inhibits growth of both HepG2 and Hep3B cell lines. The extract of I. helenium is cytotoxic to colon, breast, pancreatic, and astrocytoma cancer cell lines (Dorn et al, 2006;Tepkeeva et al, 2008). C. cassia extracts inhibit colon cancer cells and hepatocellular carcinomas, and C. cassia and A. gigas inhibit solid tumor growth (Kwon et al, 1998;Lee et al, 2003Lee et al, , 2007Moon et al, 2006) and induces apoptosis in HL-60 cells (Ka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Antitumor effects of peptide extracts from H. perforatum and a mixture of Chelidonium majus L., Inula helenium L., Equisetum arvense L., and Inonotus obliquus on slowly growing mammary adenocarcinoma in CBRB-Rb have also been studied. The antitumor effect of a single injection of the test peptides was evaluated by the delay of the appearance and growth of palpable breast cancer in mice over 4 weeks and exhibited maximum activity (Tepkeeva et al, 2008).…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Peptide extracts were prepared as described previously [3,4] and quantitatively characterized by methods of amino acid and carbohydrate analysis [1,2]. According to quantitative amino acid analysis, extracts primarily consisted from peptides (85-95%) and contained less than 5-10% carbohydrates.…”
Section: Peptidementioning
confidence: 99%